The Role of Active Polymerase Enzyme as a Model Material in the Study of the Algae DNA Replication System - Yusufjonova Munisa Abdumannob qizi (American Journal of Biology and Natural Sciences, 2025)
This scientific work extensively explores the potential of using the Taq polymerase enzyme as a model in studying the DNA replication system of algae. The structural and functional properties of thermostable DNA polymerases serve as an important tool in the in-depth study of the genetic system of algae. The results of this study form a new scientific approach to determining the stability of the algal genome, their replication mechanism, and their biotechnological significance